2011
DOI: 10.4028/www.scientific.net/amr.332-334.837
|View full text |Cite
|
Sign up to set email alerts
|

The Axial Warp-Knitted Fabric and its Reinforced Composite

Abstract: The structure and performance of the axial warp-knitted composite were introduced, including bi-axial and multi-axial organizations. According to the unique structure of this fabric, the mechanical properties and the advantages as a composite reinforcement were compared with regular staple woven fabrics. The advantages of composites reinforced by bi-axial and multi-axial knitted fabrics were discussed and the applications of such advanced materials were briefly presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the following 10 years, many scholars studied the properties of axial warp-knitted fabrics with diverse means and techniques. Bu et al 3 discussed the advantages of biaxial and multi-axial knitted fabric-reinforced composites and briefly introduced the applications of such advanced materials in 2011. Ma et al 4 tested the tensile and tear properties of CWK (Co-woven-knitted) fabrics in different directions, and the curves and damage factures indicated that the knitting loops had an obvious influence on the mechanical behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the following 10 years, many scholars studied the properties of axial warp-knitted fabrics with diverse means and techniques. Bu et al 3 discussed the advantages of biaxial and multi-axial knitted fabric-reinforced composites and briefly introduced the applications of such advanced materials in 2011. Ma et al 4 tested the tensile and tear properties of CWK (Co-woven-knitted) fabrics in different directions, and the curves and damage factures indicated that the knitting loops had an obvious influence on the mechanical behaviors.…”
mentioning
confidence: 99%
“…Bu et al. 3 discussed the advantages of biaxial and multi-axial knitted fabric-reinforced composites and briefly introduced the applications of such advanced materials in 2011. Ma et al.…”
mentioning
confidence: 99%